Response of rice phenology to climate warming weakened across China during 1981–2018: did climatic or anthropogenic factors play a role? - Liangliang Zhang; Zhao Zhang; Jing Zhang; Yuchuan Luo; Fulu Tao (Environmental Research Letters, 2022)
Climate warming has substantially shifted plant phenology, which alters the length of growing season and consequently affects plant productivity. Recent studies showed a stalled or reversed impact of climate change on vegetation phenology since 1998, as well as an asymmetric warming effect. However, how field crop phenology responded to the recent climate warming and the asymmetric warming remains unknown. In addition, the relative roles of climate change, sowing date and cultivars shifts in the spatiotemporal changes of crop phenology at different regions need to be better understood. Here, using the latest 9,393 phenological records at 249 agro-meteorological stations across China over 1981–2018, we critically investigated the spatiotemporal dynamics of rice phenology and disentangled the effects of different drivers by exploiting the physiological relationship between crop phenology and thermal accumulation. The results showed that length of growing period (GP) increased by 3.24 ± 0.15 days/decade for single rice, 1.90 ± 0.22 days/decade for early rice and 0.47 ± 0.14 days/decade for late rice. Although climate warming during rice GP did not slow down, the trends in rice GP and the correlations between GP and temperature decreased generally from 1981–1999 to 2000–2018. The weakened phenological response to climate change was mainly caused by agronomic managements, especially cultivar shifts. Climate warming shortened GP by 0.84 ± 1.80, 1.23 ± 0.77, and 1.29 ± 1.24 days/decade for single rice, early rice and late rice, respectively. However, cultivar shifts prolonged it respectively by 3.28 ± 3.68, 2.15 ± 2.38, and 2.31 ± 3.36 days/decade, totally offsetting the negative effects of climate warming. Rice responded to daytime and night-time warming differently with night-time temperature affecting GPs more. Our study provided new insights that rice phenology responded to night-time warming more than daytime warming across China however the response to climate warming weakened, and cultivar shifts outweighed climate change in affecting rice phenology.